Ephemeral cartography: on mapping sound. Issue 2 (3rd July 2018) - McMurray, Peter
ABSTRACT: With the concurrent rise of internet cartography (e.g. Google Maps) and low-cost digital audio recording devices, soundmapping has become a widespread phenomenon. But soundmapping has a much longer history, reaching back centuries and arguably millennia. Taking a kind of media archaeological approach to such cartographic practices, I consider a number of approaches that have been used historically in systematically combining sound and mapping and offer a rough media taxonomy to elucidate the particular relationships between them (e.g. mappings in sound, of sound, etc.). I begin with Homeric epic and then move through medieval mappae mundi, Ottoman nautical charts, linguistic atlases and sonar. My historical endpoint is a cluster of practices that (usually implicitly) constitute the beginning of contemporary analysis of soundmapping: the soundscape, both in its well-known form, as articulated by Murray Schafer, but also in the work of Michael Southworth, whose ground-breaking mapping practices influenced Schafer's own ideas about sonic cartography. Beyond this archaeological rethinking of origins, I also seek to rethink mapping generally from the perspective of soundmapping: not only do soundmaps remind us of the audiovisual mediations of mapping more generally, they specifically assert the temporality of experiencing all maps, whether explicitly sonic or not.